Corporate growth and industrial dynamics: Evidence from French manufacturing - Giulio Bottazzi; Alex Coad; Nadia Jacoby; Angelo Secchi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2007)
This work explores basic properties of the size and growth rates distributions of firms at the aggregate and disaggregate levels. Using an extensive dataset on French manufacturing firms, we investigate which properties of firm size distributions and growth dynamics characterize the aggregate dynamics and are, at the same time, robust under disaggregation. Our analysis is based on non-linear robust regression methods which have never been applied before to this kind of data. The growth rates distributions we observe are well described by a Subbotin distribution with a shape parameter significantly lower than 1, suggesting a noticeable departure from the Laplace behavior reported in previous works on Italian and US data. At the same time, the variance of growth rates depends negatively on size and the relationship does not seem to be linear, with larger firms possibly displaying lower variability in their growth dynamics. At the disaggregate level, we observe significant heterogeneity in the firm size distributions across sectors while the shape of the sectoral growth rates density displays a surprising degree of homogeneity.
Keywords: 330